Resident readiness. - Klamen, Debra L.; Hingle, Susan Thompson (McGraw-Hill Education/Medical, 2013)
Practical, case-based preparation for the internal medicine residency experience, this book is designed to prepare medical students for the full range of clinical scenarios they will encounter during their internal medicine residency. Entirely case-based, the book presents clinical scenarios followed by questions with detailed answer explanations. Also included is discussion of the clinical problem-solving process, clinical pearls highlighting key points, and comprehension questions.